A scoping review of small animal image-guided radiotherapy research: Advances, impact and future opportunities in translational radiobiology. (May 2022) - Brown, Kathryn H.; Ghita, Mihaela; Dubois, Ludwig J.; de Ruysscher, Dirk; Prise, Kevin M.; Verhaegen, Frank; Butterworth, Karl T.
Highlights: Research trends from 15 years of preclinical image-guided radiotherapy (RT). Progress in preclinical RT research classified by physics & biology contributions. Translational impact of preclinical radiobiology research. Abstract: Background and purpose: To provide a scoping review of published studies using small animal irradiators and highlight the progress in preclinical radiotherapy (RT) studies enabled by these platforms since their development and commercialization in 2007. Materials and methods: PubMed searches and manufacturer records were used to identify 907 studies that were screened with 359 small animal RT studies included in the analyses. These articles were classified as biology or physics contributions and into subgroups based on research aims, experimental models and other parameters to identify trends in the preclinical RT research landscape. Results: From 2007 to 2021, most published articles were biology contributions (62%) whilst physics contributions accounted for 38% of the publications. The main research areas of physics articles were in dosimetry and calibration (24%), treatment planning and simulation (22%), and imaging (22%) and the studies predominantly used phantoms (41%) or in vivo models (34%). The majority of biology contributions were tumor studies (69%) with brain being the most commonly investigated site. The most frequently investigated areas of tumor biology were evaluating radiosensitizers (33%), model development (30%) and imaging (21%) with cell-line derived xenografts the most common model (82%). 31% of studies focused on normal tissue radiobiology and the lung was the most investigated site. Conclusions: This study captures the trends in preclinical RT research using small animal irradiators from 2007 to 2021. Our data show the increased uptake and outputs from preclinical RT studies in important areas of biology and physics research that could inform translation to clinical trials.